GLP-1 enhances hyperpolarization-activated currents of mouse cerebellar Purkinje cell in vitro - Liu, Yang; Cao, Li-Xin; Wang, Wei-Yao; Piao, Yong-Rui; Wang, Jun-Ya; Chu, Chun-Ping; Bing, Yan-Hua; Qiu, De-Lai (Frontiers in Molecular Neuroscience, 2023)
Glucagon-like peptide-1 (GLP-1) is mainly secreted by preglucagonergic neurons in the nucleus tractus solitarius, which plays critical roles in regulation of neuronal activity in the central nervous system through its receptor . In the cerebellar cortex, GLP-1 receptor is abundantly expressed in the molecular layer, Purkinje cell (PC) layer and granular layer, indicating that GLP-1 may modulate the cerebellar neuronal activity. In this study, we investigated the mechanism by which GLP1 modulates mouse cerebellar PC activity in vitro. After blockade of glutamatergic and GABAergic synaptic transmission in PCs, GLP1 increased the spike firing rate accompanied by depolarization of membrane potential and significantly depressed the after-hyperpolarizing potential and outward rectifying current of spike firing discharges via GLP1 receptors. In the presence of TTX and Ba2+, GLP1 significantly enhanced the hyperpolarized membrane potential-evoked instant current, steady current, tail current (I-tail) and hyperpolarization-activated (IH) current. Application of a selective IH channel antagonist, ZD7288, blocked IH and abolished the effect of GLP1 on PC membrane currents. The GLP1 induced enhancement of membrane currents was also abolished by a selective GLP1 receptor antagonist, exendin-9-39, as well as by protein kinase A (PKA) inhibitors, KT5720 and H89. In addition, immunofluorescence detected GLP1 receptor in the mouse cerebellar cortex, mostly in PCs. These results indicated that GLP1 receptor activation enhanced IH channel activity via PKA signaling, resulting in increased excitability of mouse cerebellar PCs in vitro. The present findings indicate that GLP1 plays a critical role in modulating cerebellar function by regulating the spike firing activity of mouse cerebellar PCs.